New electronic apex locator Romiapex A-15 presented accuracy for working length determination in permanent teeth - Etevaldo Matos Maia Filho; Cláudia de Castro Rizzi; Daniela Silva Barroso de Oliveira; Paulo Nelson Filho; Raquel Assed Bezerra da Silva; Léa Assed Bezerra da Silva (University Library System, University of Pittsburgh, 2014)
Purpose: The present study aims to evaluate, ex vivo, the accuracy of electronic apex locators Root ZX II and Romiapex-15, for working length (WL) determination in permanent teeth. Materials and Methods: Fourteen single-rooted teeth (incisors and canines), with their apices fully formed were used. The dental crowns were removed. The anatomic length of the tooth (real measurement) was visually determined through the insertion of a size 10 K-file until the tip of the instrument could be observed in the apical foramen under a microscope (20X). Teeth were fixed in a model of resin and adapted into alginate soaked with saline solution, which was used as an  electrical conductor. Using a K-file, root canals were measured electronically using both devices. The results obtained for each apex locator were compared to the real measurements. The accuracy between the devices was statistically analyzed using the Bland-Altman graph, Intraclass Correlation Coefficient (ICC), and Student's t-test. Results: The mean difference between the measurements using the Root ZX II was 0.277mm greater than the real measurement, while the measurements from the Romiapex-15 were 0.308mm higher on average. The comparison between Root ZX II and Romiapex-15 had no significant difference (p= 0.868). Conclusion: It was concluded that Root ZX II and Romiapex-15 had similar accuracy. Romiapex-15 could be an option for WL determination in permanent teeth.